The Nuclear Receptor Rev-erbα Controls Circadian Thermogenic Plasticity - Gerhart-Hines, Zachary (2013)
Circadian oscillation of body temperature is a basic, evolutionary-conserved feature of mammalian biology(1). Additionally, homeostatic pathways allow organisms to protect their core temperatures in response to cold exposure(2). However, the mechanism responsible for coordinating daily body temperature rhythm and adaptability to environmental challenges is unknown. Here we show that the nuclear receptor Rev-erbα, a powerful transcriptional repressor, links circadian and thermogenic networks through the regulation of brown adipose tissue (BAT) function. Mice exposed to cold fare dramatically better at 5 AM (Zeitgeber time 22) when Rev-erbα is barely expressed than at 5 PM (ZT10) when Rev-erbα is abundant. Deletion of Rev-erbα markedly improves cold tolerance at 5 PM, indicating that overcoming Rev-erbα-dependent repression is a fundamental feature of the thermogenic response to cold. Physiological induction of uncoupling protein 1 (UCP1) by cold temperatures is preceded by rapid down-regulation of Rev-erbα in BAT. Rev-erbα represses UCP1 in a brown adipose cell-autonomous manner and BAT UCP1 levels are high in Rev-erbα-null mice even at thermoneutrality. Genetic loss of Rev-erbα also abolishes normal rhythms of body temperature and BAT activity. Thus, Rev-erbα acts as a thermogenic focal point required for establishing and maintaining body temperature rhythm in a manner that is adaptable to environmental demands.